Iron Uptake Controls Trypanosoma cruzi Metabolic Shift and Cell Proliferation - Claudia F. Dick; Carolina L. Alcantara; Luiz F. Carvalho-Kelly; Marco Antonio Lacerda-Abreu; Narcisa L. Cunha-; José R. Meyer-Fernandes; Adalberto Vieyra (MDPI AG, 2023)
(1) Background: Ionic transport in Trypanosoma cruzi is the object of intense studies. T. cruzi expresses a Fe-reductase (TcFR) and a Fe transporter (TcIT). We investigated the effect of Fe depletion and Fe supplementation on different structures and functions of T. cruzi epimastigotes in culture. (2) Methods: We investigated growth and metacyclogenesis, variations of intracellular Fe, endocytosis of transferrin, hemoglobin, and albumin by cell cytometry, structural changes of organelles by transmission electron microscopy, O2 consumption by oximetry, mitochondrial membrane potential measuring JC-1 fluorescence at different wavelengths, intracellular ATP by bioluminescence, succinate-cytochrome c oxidoreductase following reduction of ferricytochrome c, production of H2O2 following oxidation of the Amplex® red probe, superoxide dismutase (SOD) activity following the reduction of nitroblue tetrazolium, expression of SOD, elements of the protein kinase A (PKA) signaling, TcFR and TcIT by quantitative PCR, PKA activity by luminescence, glyceraldehyde-3-phosphate dehydrogenase abundance and activity by Western blotting and NAD+ reduction, and glucokinase activity recording NADP+ reduction. (3) Results: Fe depletion increased oxidative stress, inhibited mitochondrial function and ATP formation, increased lipid accumulation in the reservosomes, and inhibited differentiation toward trypomastigotes, with the simultaneous metabolic shift from respiration to glycolysis. (4) Conclusion: The processes modulated for ionic Fe provide energy for the T. cruzi life cycle and the propagation of Chagas disease.